Software for the thermal and hydraulic design of plate heat exchangers - Ju, Jianing (Nanyang Technological University, 2022)
Plate Heat Exchangers (PHEs) are a prevalent type of heat exchangers used by various industries. As there has not been a unified set of design methods for PHEs due to their diverse design configurations, software applications that automate the lengthy and repetitive calculations are mostly commercial software that are not available to students and researchers. In this project, a software application for the rating and sizing calculations of PHEs is developed. Rating designs provide performance ratings such as outlet temperatures and pressure drops, given the operating conditions of a PHE. Sizing designs suggest the appropriate size of a PHE such as the total surface area and the number of plates, given the desired requirements of the heat transfer process. The design methods employed follow the rating calculations in the textbook by Kakac et al. and the sizing calculation in the article by Mehrabian. The software is a web application that can be accessed through a public URL: https: //papaya-bubblegum-9152ac.netlify.app, on any device with internet access. The front end section of this application is developed with "React" in JavaScript, while the back end section is developed in the JavaScript environment "Node.js". Apart from design calculations, the software has a record management system that enables users to save their designs and access them later. User data is persistently stored in a MySQL database for later retrieval. Several features are developed that can enhance the usability and integrity of the software. Rigorous validations are conducted on the design parameters entered by the user, with suggestions on valid input ranges. The batch input and batch export functions make possible a design pipeline that allows multiple designs to be filled out, calculated, and saved concurrently. The program calculations have been validated by comparing the program results with hand calculations. The outcomes of hand calculations match the ones produced by the software, proving the correctness and reliability of the calculations. To further improve on the current software in the future, an expansion of design scenarios and improvements on the user experience can be considered. Design procedures involving fluids under a phase change can be included. Graphical representations of the design process as well as the end results can also be developed.